Two New Leaf Spot Diseases of Bael (Aegle marmelos Correa) from Uttar Pradesh (Indian Journal of Arid Horticulture, 2025)
Aegle marmelos Correa, commonly known as bael, is one of the most significant medicinal plants of India. It thrives under adverse agro-climatic conditions and can adapt successfully to a wide range of habitats, from arid and semi-arid to mesophytic conditions. It also exhibits a wide temperature tolerance, ranging from 4°C to 48°C. The importance of Aegle marmelos lies in its curative properties, making it one of the most valuable medicinal plants in India.
Keywords: Occurrence; Disease